Advanced Hydrogels for the Controlled Delivery of Insulin - Shazia Mansoor; Pierre P. D. Kondiah; Yahya E. Choonara (MDPI AG, 2021)
Insulin is a peptide hormone that is key to regulating physiological glucose levels. Its molecular size and susceptibility to conformational change under physiological pH make it challenging to orally administer insulin in diabetes. The most effective route for insulin delivery remains daily injection. Unfortunately, this results in poor patient compliance and increasing the risk of micro- and macro-vascular complications and thus rising morbidity and mortality rates in diabetics. The use of 3D hydrogels has been used with much interest for various biomedical applications. Hydrogels can mimic the extracellular matrix (ECM) and retain large quantities of water with tunable properties, which renders them suitable for administering a wide range of sensitive therapeutics. Several studies have demonstrated the fixation of insulin within the structural mesh of hydrogels as a bio-scaffold for the controlled delivery of insulin. This review provides a concise incursion into recent developments for the safe and effective controlled delivery of insulin using advanced hydrogel platforms with a special focus on sustained release injectable formulations. Various hydrogel platforms in terms of their methods of synthesis, properties, and unique features such as stimuli responsiveness for the treatment of Type 1 diabetes mellitus are critically appraised. Key criteria for classifying hydrogels are also outlined together with future trends in the field.